Environmental Management and Construction Waste Strategies in Malaysia: An Overview of Green Materials and Waste Management Challenge - Lie, Michael; Tam, Nicholas; Talukdar, Gaurav (Industrial and Domestic Waste Management, 2024)
This review provides an overview of Malaysia's environmental management practices, with a focus on construction waste management, to address the country's growing waste generation in the construction sector. The paper highlights key challenges Malaysia faces in implementing effective environmental practices and offers potential solutions to overcome these hurdles. Additionally, it examines the use of green materials, such as recycled concrete aggregate and bamboo, which have demonstrated significant potential in reducing resource consumption and carbon emissions. The challenges of adopting these materials are analyzed, along with a discussion of their advantages and limitations. Ultimately, the review underscores the importance of environmental management and the role of sustainable materials in transforming Malaysia’s construction industry, while calling for stronger regulatory frameworks and industry collaboration to address these challenges. The objective of this review is to provide insights into the current environmental management efforts in Malaysia and to explore the potential of green materials in mitigating environmental impacts.